(untitled) (Bangladesh Journal of Botany, 2019)
Populations of Azospirillum and Azotobacter isolated and identified from the soil rhizosphere of Acacia ehernbergiana, A. gerrardii and A. tortilis from three sites varied widely irrespective of tree species, size and site. Azospirillum strains were purified and characterized through morphological, microscopic and biochemical tests for motility, cell shape, pigmentation, colony color, gram reaction, optimal temperatures, biotin requirement, pH growth, acidification of peptone glucose medium, ability of nitrogen fixation, growth on 3% NaCl, and D-glucose and D-ribose utilization. Twenty Azospirillum isolates were divided into four matching characters. They were identified as A. lipoferum, A. brasilense, A. dobereinerae and A. zeae. The same above tests with omission of temperatures, biotin requirement, and acidification of peptone and addition of starch hydrolysis, H2S, urease, oxidase and sucrose, maltose and mannitol as carbon source were applied to Azotobacter strains. Azotobacter isolates were divided into three matching characters. They were identified as A. chroococcum, A. beijerinckii and A. salinestris.